"Far North Features Pictured by the Bartlett-Academy of Natural Sciences Expedition to Greenland" (Philadelphia Evening Bulletin, 1930)
"Chief engineer Jim Dove is giving Captain Robert Bartlett, of the expedition's ship and skipper of the late Admiral Perry's Roosevelt, a haircut, on the deck of the Morrissey." With clipping